A multi-dimensional exploration of spirituality to empathy. Issue 4 (2nd October 2021) - Stewart, Chris; Lawrence, Shawn
ABSTRACT: Empathy is a well-established factor for a successful therapeutic relationship. Similarly, spirituality has demonstrated significance for many clinical outcomes. Although available evidence generally supports a relationship between spirituality and empathy, there is a dearth of empirical information examining the relationship from a multidimensional perspective. The Expressions of Spirituality Inventory-Revised (ESI-R) and Interpersonal Reactivity Index (IRI) were used with a sample of both students and practitioners. Testing demonstrated a significant difference between students and practitioners for dimensions of both spirituality and empathy. Results confirmed that two ESI-R dimensions produced significant regression models with several IRI dimensions for both students and practitioners.